The Effect Of Seawater Evaporation On The Visibility Of The Cross-Crescent (Case Study of Loang Baloq Beach, Mataram) - Nur mahmudi Qiromi (Abdi Masyarakat, 2026)
The visibility of the crescent moon is a crucial factor in the crescent moon sighting (rukyatul hilal) to determine the beginning of the lunar month. Ideally, crescent moon observations should be conducted in a location with a clean and transparent atmosphere, but these conditions are often lacking in coastal areas affected by seawater evaporation. This study aims to analyze the effect of seawater evaporation on crescent moon visibility at Loang Baloq Beach, Mataram City, one of the official crescent moon sighting locations in West Nusa Tenggara Province. This study uses a field research method (field research) with a qualitative approach. Data were obtained through observation, interviews, documentation, and meteorological data from the Meteorology, Climatology, and Geophysics Agency (BMKG) covering evaporation, air humidity, air pressure, and reports of the results of the crescent moon sighting. The results showed that the rate of seawater evaporation at Loang Baloq Beach is relatively high, ranging from 123–169 mm per month, with an average atmospheric humidity of 84.5%. This condition increases the content of water vapor and atmospheric aerosols, which causes a decrease in sky transparency and a decrease in the contrast of the crescent moon against the background of the twilight sky. This relationship forms a series of processes, including seawater evaporation, increased atmospheric water vapor, increased air humidity, decreased sky transparency, reduced crescent moon contrast, and decreased chances of successful sighting. This study concludes that seawater evaporation is one of the atmospheric factors that contribute to the visibility of the crescent moon in coastal areas, although it is not the only determining factor in the success of the observation